2010
DOI: 10.1007/s00330-010-1927-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and fibre tracking in cervical spondylotic myelopathy

Abstract: FA values were significantly correlated with some of the patients' clinical scores. High signal intensity of the spinal cord on T2 was not correlated either with the DTI parameters or with the clinical assessment, suggesting that FA is more sensitive than T2 imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
116
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 30 publications
16
116
0
Order By: Relevance
“…Cerebrospinal fluid flow disturbances, resulting from degenerative changes both in static position and during movement, could increase the pressure around the spinal cord and, in turn, alter interstitial diffusion which would result in DTI metrics changes [6]. The differences in FA and ADC values between control group and groups representing advanced, degenerative changes (D, E) were obvious, and has been already described by many authors [1,[6][7][8][13][14][15].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Cerebrospinal fluid flow disturbances, resulting from degenerative changes both in static position and during movement, could increase the pressure around the spinal cord and, in turn, alter interstitial diffusion which would result in DTI metrics changes [6]. The differences in FA and ADC values between control group and groups representing advanced, degenerative changes (D, E) were obvious, and has been already described by many authors [1,[6][7][8][13][14][15].…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, DTI seems to be sensitive to pathological processes altering water diffusion at a microscopic level, far beyond the resolution of conventional MR imaging [13]. Several investigators have carried out DTI studies in patients suffering from CSM [1,[6][7][8][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…6 This raises the possibility of using DT imaging to distinguish patients with permanent myelopathic injury, reversible myelopathic injury, and absence of myelopathic change. Budzik et al 5 correlated mJOA scores with DT imaging results in 20 patients with CSM and found lower FA values in those with worse clinical function. The mean upper-and lower-extremity mJOA scores of 76.1 and 63.4, respectively, in this mildly affected population underscore the high sensitivity of DT imaging in detecting white matter damage.…”
Section: Clinical Application Of Dt Imagingmentioning
confidence: 99%
“…Recent developments in MR pulse sequence design have greatly reduced these problems (Thurnher and Law 2009;Wilm, Gamper et al 2009;Wilm, Svensson et al 2007). Clinical findings correlate with DTI metrics of the injured spinal cord (Budzik, Balbi et al 2011;Chang, Jung et al 2010;Kim, Loy et al 2010;Qian, Chan et al 2011). Few studies have explored the relationship between structural integrity, evaluated using DTI, and physiological function of the human spinal cord Kerkovsky, Bednarik et al 2011;Qian, Chan et al 2011).…”
Section: Introductionmentioning
confidence: 99%